THE ROLE OF THE QUR’AN IN THE EDUCATIONAL DEVELOPMENT OF PRIMARY SCHOOL CHILDREN (PIONIR: JURNAL PENDIDIKAN, 2025)
Primary school children's education is the main foundation that will shape their character, knowledge and skills throughout life. The Qur'an plays a crucial role in shaping children's education. Beyond serving as a spiritual guide for Muslims, the Qur’an is a comprehensive source of moral values, character development, ethics and knowledge. This study highlights essential teachings from the Qur’an that should instilled in children from an early age, including obedience to parents (QS. Al-Isra:23-24), monotheism (QS. Luqman:13), adherence to Allah’s commands,and noble character (akhlaqul karimah) (QS. At-Tahrim: 6).Keywords: Al-Qur'an, Moral Education, Character Development, Islamic Studies, Primary Education
Keywords: Al-Qur'an; Education; Elementary School